2008
DOI: 10.1177/1043659607312968
|View full text |Cite
|
Sign up to set email alerts
|

The Learning Experiences of Taiwanese Nursing Students Studying in Australia

Abstract: Increasing numbers of international students from Asia are attracted to Australian higher education institutions. For many of these students, English is their second language (ESL). This article describes the experiences of 21 Taiwanese baccalaureate and graduate nursing students studying at Australian universities. Using a qualitative framework, semistructured interviews were conducted in the students'first language. The Chinese and English translations of the transcripts were analyzed using thematic content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
71
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(85 citation statements)
references
References 27 publications
10
71
0
Order By: Relevance
“…Wang et al reported on the effect of LEP on students in their study, 'As a consequence of this, students were unable to articulate their thoughts and express themselves in written assignments and verbal presentations' (Wang et al 2008, 147). In the current study, we also found that these language-related challenges are expressed in somewhat similar forms to those reported by Wang et al (2008), ranging from communication skills difficulties to struggles with academic writing abilities. If international students experience such language competency gaps it stands to reason that their academic performance is bound to be compromised (Beoku-Betts 2004).…”
Section: I'm Not Confident About My English But I Try To Participatesupporting
confidence: 55%
“…Wang et al reported on the effect of LEP on students in their study, 'As a consequence of this, students were unable to articulate their thoughts and express themselves in written assignments and verbal presentations' (Wang et al 2008, 147). In the current study, we also found that these language-related challenges are expressed in somewhat similar forms to those reported by Wang et al (2008), ranging from communication skills difficulties to struggles with academic writing abilities. If international students experience such language competency gaps it stands to reason that their academic performance is bound to be compromised (Beoku-Betts 2004).…”
Section: I'm Not Confident About My English But I Try To Participatesupporting
confidence: 55%
“…International students, in particular, reported not knowing what was expected of them (Wang et al, 2008). Brown (2008) and Williams and Calvillo (2002) added to this by demonstrating that culturally diverse students are keen on to receive timely and frequent feedback on their success.…”
Section: Literature Reviewmentioning
confidence: 86%
“…According to Chapman and Pyvis (2006), students' experiences of being part of the community contributed to their experience of the quality of their education. Studies involving students from ethnic or linguistic minorities reported students' current or former experiences of prejudice and discrimination (Amaro et al, 2006;Bheenuk et al, 2007;Sanner and Wilson, 2008;Wang et al, 2008).…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…Apart from being often stereotyped as handicapped, bewildered, and lacking English language ability and familiarity with the education system (Mestenhauser, 1983;Paige, 1990;Pedersen, 1991), they also face other negative stereotypes associated with their ethnicity and cultural background (Lee & Rice, 2007;Spencer-Rodgers, 2001). In this context they are often targets of racism (Yoon & Portman, 2004), face several other forms of PERCEIVED DISCRIMINATION AND ACCULTURATION STRATEGIES 4 discrimination (Bonazzo & Wong, 2007;Lee & Rice, 2007;Schmitt, Spears, & Branscombe, 2003;Sherry, Thomas, & Chui, 2010;Ward, Bochner, & Furnham, 2001;Yeh & Inose, 2003), and are also victims of exclusion, isolation, and unfriendliness from domestic students (Gu, Schweisfurth, & Day, 2010;Wang, Singh, Bird, & Ives, 2008). In the present research we focused on these perceptions.…”
mentioning
confidence: 99%